Edukasi Pengelolaan Sampah pada Lokasi Wisata Bahari Kelompok Sadar Wisata Pantai Barane Kecamatan Banggae Timur - Noor, Rahmat Januar; Nur, Fauzia; Mahfud, Chairul Rusyd; Nasyrah, Adiara Firdhita Alam; Ihsan, Muhammad Nur (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The issue of marine debris is part of the Sustainable Development Goals (SDGs) topic, especially on agenda 12 related to responsible consumption and production and agenda 14 marine ecosystems. The existence of community activities on the coast including tourism can be a source of marine debris problems because they contribute to the increase in waste from tourists. Barane Beach, Majene Regency is a tourism development area where one of the groups actively managing the area is the Barane Beach Tourism Awareness Group (POKDARWIS). The method of implementing activities using the counseling method and technology procurement includes three stages, namely: (1) coastal clean-up action, (2) waste management education, and (3) procurement of separate trash bins. The results of the education activities show an increase in public perception regarding the cleanliness of waste at coastal tourist locations and a good understanding of waste management.